A Convenient Route to Mixed Pnictogenylboranes. Issue 41 (5th September 2017) - Hegen, Oliver; Marquardt, Christian; Timoshkin, Alexey Y.; Scheer, Manfred
Abstract: We report on the synthesis and characterization of mixed pnictogenylboranes. The substitution of the Lewis base SMe2 in (OC)5 W–PH2 BH2 –SMe2 (2 ) by different pnictogenylboranes ER2 BH2 –LB (E=P, As, Sb) leads to the Lewis acid/base stabilized butane analogue (OC)5 W–PH2 BH2 ER2 BH2 –LB (3 a, b : E=P; R=H, SiMe3 ; LB=NMe3 ; 4 a, b : E=As; R=H, SiMe3 ; LB=NMe3 ; 5 : E=Sb; R=SiMe3 ; LB=NHC Me ). All of these compounds were characterized by single‐crystal X‐ray structure analysis, mass spectrometry, NMR, and IR spectroscopy. In addition, the very unstable phosphanylborane chain PH2 BH2 PH2 BH2 –NMe3 (1 ) was synthesized. DFT calculations provide insight into the thermodynamics of these reactions. Abstract : Mashed up : Novel neutral pnictogenylboranes (OC)5 W–PH2 BH2 ER2 BH2 –LB (E=P, As, Sb; R=H, SiMe3 ) were obtained by making use of donor/acceptor stabilization. The substitution of SMe2 in (OC)5 W–PH2 BH2 –SMe2 with Lewis base stabilized pnictogenylboranes enabled the isolation of the first neutral molecules possessing a P‐B‐As‐B chain or a P‐B‐Sb‐B unit.